The Consumer Expectation Test under the Consumer Protection Act 1999: a viable test for determining the quality and safety of products? - Amin, Naemah (Sweet & Maxwell Asia, 2008)
Protection against sub-standard and unsafe products is one of the most important components in consumer protection law. It has thus been reflected in the Malaysian Consumer Protection Act 1999 (hereinafter referred to as the CPA) which provides several sections relating to quality and safety of consumer products. However in determining product quality and safety, the CPA adopts the so called "Consumer Expectation Test". Under this test, the product is considered defective if a reasonable consumer would find it defective. Whether the test could provide a readily ascertainable objective standard against which the quality and safety of a product can be measured by relevant parties is highly debatable. It is the aim of this paper to examine the nature of the consumer expectation test and its viability in setting a proper standard of product quality and safety. Since case law on the subject has not yet developed in Malaysia, reference will be made to the application and development of the test in other jurisdictions, particularly the UK and USA. The paper also considers alternative tests which are deemed to be more appropriate.